–The role of audit review and the preparation of reports in the organization of insurance business in Iraq – applied research in the Office of Insurance and a sample of Iraqi insurance companies - Abbas, Maryam Muzahim; WaHeib, Hamza Faik (Journal of Economic, Administrative and Legal Sciences, 2019)
Insurance companies are considered as the most important institutions for the savings container and the safety valve for the economy, so they must be subject to a proper regulatory system to ensure that they comply with the legislations and standards regulating their work and to ensure their work in accordance with the exact and in accordance with the processes and legislations, including the most important international standards for supervising insurance companies (26) principles issued by the International Organization for the Supervision of Insurance Companies (IAIS). The research dealt with the audit review and preparation of reports in addition to the organization of business and its foundations and the reasons for organizing insurance business and the international and local supervisory bodies of insurance companies and reaching conclusions and recommendations. The practical aspect included the preparation of the examination form, including a set of instructions and controls for the insurance sector to determine the extent of their application by the regulatory body responsible for supervision and supervision of the insurance companies and the research sample represented by the Iraqi insurance company, the National Insurance Company, Insurance. The research reached a number of conclusions, the most prominent of which is the weakness of the supervisory role of the insurance department of the insurance companies and the failure to apply the international standards for supervising the insurance companies, although stipulated in the Insurance Law No. 10 of 2005. The research reached a number of recommendations, most notably, the necessity of activating the supervisory role of the Insurance Bureau of the insurance companies. The application of the international standards for supervising the insurance companies as stipulated in the Insurance Law No. 10 of 2005.